PROSPECTS OF WOMEN ENTREPRENURS IN TENKASI DISTRICT: AN ANALYTICAL STUDY (International Journal of Food and Nutritional Sciences, 2022)
It is their careers that play an important role in the advancement of women. Financial freedom is every woman’s dream. Such financial independence can only be achieved by woman entrepreneurship. In today's era, there are many prospects for woman entrepreneurship.This study investigates the prospects of women entrepreneurs in Tenkasi district, focusing on socio-economic factors that influence their entrepreneurial endeavors. Tenkasi, located in the southern part of Tamil Nadu, India, presents a unique socio-economic landscape where cultural traditions intersect with modern economic opportunities. By examining the intersection of gender dynamics, economic development, and cultural norms, this study aims to provide insights into the opportunities and challenges faced by women entrepreneurs in the region.Key factors influencing the prospects of women entrepreneurs in Tenkasi district include access to finance, educational opportunities, networking resources, market demand, infrastructure development, and socio-cultural attitudes towards women in business. Government initiatives aimed at promoting women's entrepreneurship, such as financial assistance schemes and skill development programs, play a crucial role in shaping the entrepreneurial ecosystem.The elements influencing the Prospects of Women entrepreneurs were ascertained through semi-structured interviews. After selecting 144women entrepreneurs from the Tenkasi district using a suitable sample technique, the researchers performed theme analysis to analyze the transcripts of their interviews.